Immunofluorescence Studies on the Pathogenesis of Intestinal Chlamydial Infections in Calves - Eugster, A. K. (1970)
Newborn calves were exposed orally to the chlamydial agent of bovine polyarthritis. The chlamydial infection in the gastrointestinal tract was traced by reisolation of the agent and by fluorescent-antibody techniques. Absorption of the fluorescein isothiocyanate (FITC)-labeled antiserum with bovine fetal intestinal tissue powder eliminated effectively the nonspecific fluorescence of eosinophilic granules in intestinal tissue sections. Cells of the eosinophilic series were observed in great numbers in the gastrointestinal tract of inoculated and normal calves. Although chlamydial agents could be reisolated from mucosal scrapings of abomasum and duodenum for 5 days after inoculation, specific fluorescence was not observed in these gastrointestinal portions. As the chlamydial infection progressed, it localized in the mucosal epithelial cells of the jejunum and ileum. Fluorescing chlamydial inclusions were observed most consistently in the cytoplasm of mucosal epithelial cells on the tips of the jejunal and ileal villi. The inclusions were located between the nucleus and the free border of the epithelial cells. In the deeper parts of the villi, the inclusions in the epithelial cells were situated frequently between the nucleus and the basement membrane of the mucosal lamina propria. In calves examined 7 days after inoculation, fluorescing chlamydial inclusions were seen in the cells of the crypts and the mucosal lamina propria of the lower portions of the small intestine. Chlamydial infection of cells in the intestinal interstitium reflected a process of systemic invasion.